Public policy, independent television production and the digital challenge. (1st June 2019) - Doyle, Gillian
Television production is a vital component of the media and a sector whose performance has important cultural and economic ramifications. In the United Kingdom, the growing prosperity of the programme-making sector – attributable partly to historic policy interventions – is widely recognized as being a success story. However, a recent wave of corporate consolidation and takeovers, characterized by many leading UK production companies being bought out and often by US media conglomerates, has raised concern about the ability of the independent production sector to flourish in an increasingly globalized and competitive digital environment for television. Although preserving indigenous television production and associated audience access to locally made content remain important goals for media policy, achieving these has become more difficult in the face of trends towards consolidated ownership and 'the emergence of powerful transnational platforms commercialising cultural goods and services online' (García Leiva and Albornoz 2017: 10). This article examines the challenges raised for public policy as ownership structures in the television production sector adjust in response to new distribution technologies and to the transformative forces of digitalization and globalization. Focusing on the United Kingdom as an example, it asks do we still need television production companies that are indigenous and independent in a digital world and if so why? What role can and should public policy play in supporting the sustainability of an 'indie' sector? Drawing on recent original empirical research into the association between corporate configuration, business performance and content in the television production sector, it reflects critically on historic and recent approaches to sustaining independent producers and it considers how, in a digital world, public policy may need to be re-imagined for a rapidly evolving television landscape.